Carotid Artery Compression Caused by the Cochlea. Issue 7 (August 2015) - Giese, Dina; Rask-Andersen, Helge
Abstract : Hypothesis: We investigated the possible interference between the human internal carotid artery and the cochlea. Background: The cochlea and the internal carotid artery (ICA) are anatomically closely related in the human temporal bone. The intimacy may even result in functional interferences. Methods: Here, we analyzed 324 human plastic inner ear corrosion casts including the ICA canal and jugular bulb. Results: Results showed that in 23% (14 cases), the cochlea caused physical impression in the carotid canal (CA) with luminal restriction. In one case, there was no separation between the CC and the basal turn of the cochlea. The distance between the CC and the cochlea varied between 0 and 1 mm among these 14 specimens. The lumen restriction of the CC in the pyramid-axial projection varied between 39% and 79%. Conclusion: We speculate that the reduction in ICA canal lumen size caused by the cochlea may form a predilection site for intratemporal ICA plaque formation and therefore be clinically relevant.